The protective effects of Olmesartan against interleukin-29 (IL-29)-induced type 2 collagen degradation in human chondrocytes. Issue 1 (1st January 2022) - Liu, Yunlong; Liu, Junyi; Ma, Yan; Zhang, Yongyong; Chen, Qiong; Yang, Xin; Shang, Yanchun
ABSTRACT: Osteoarthritis (OA) is a cartilage degenerative disease commonly observed in the elderly population and is pathologically characterized by the degradation of the cartilage extracellular matrix (ECM). Matrix metalloproteinases (MMPs) and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTSs) are critical enzymes involved in the degradation of ECM. Olmesartan is an inhibitor of the angiotensin II receptor developed for the treatment of hypertension, and recent studies show that it exerts anti-inflammatory effects in arthritis. The present study aimed to investigate the mechanism of the protective effect of Olmesartan on cartilage ECM degradation. Interleukin-29 (IL-29) is a novel inflammatory mediator involved in the inflammation and degradation of cartilage in OA, and human T/C-28a2 cells treated with it were the inflammatory model in vitro . We found that the degradation of type 2 collagens and aggrecans was induced by IL-29, accompanied by the upregulation of MMPs and ADAMTSs, but the presence of Olmesartan significantly ameliorated these increases. In addition, Olmesartan abolished IL-29- induced oxidative stress and elevated the expression level of TNF receptor-associated factor 6 (TRAF-6). Mechanistically, we showed that Olmesartan suppressed IL-29- caused inhibitor kappa B α (IκBα) expression and nuclear translocation of nuclear factor kappa-B (NF-κB) p65, indicating it suppressed the activation of the NF-κB pathway. Collectively, our data reveal that Olmesartan exerted a protective function on IL-29- induced type 2 collagen degradation in human chondrocytes.